IDENTIFIKASI KARAKTERISTIK KAWASAN TEPIAN SUNGAI MUSI KOTA PALEMBANG (KASUS: KELURAHAN 5 ULU DAN 7 ULU) - Utomo, Arditia Larasati; Agustian, Endy; Kospa, Herda Sabriyah Dara (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2024)
The Musi River waterfront area in Palembang City has been a traditional residential settlement area since the era of the Sriwijaya Kingdom. The riverbank area has been chosen by the community as a place to reside due to the benefits of the river, which offers many potential resources and ease of river transportation access. This research aims to identify the characteristics of areas along the riverbanks in the 5 Ulu and 7 Ulu Subdistricts, Seberang Ulu 1 District, using a qualitative research approach. Data collection techniques employed include observation, interviews, and document review, followed by analysis comprising qualitative data analysis and Spradley model analysis. The research results outline that the identification of the characteristics of the Musi River waterfront area is based on both non-physical settlement aspects and physical settlement aspects. The non-physical settlement aspects describe that the research area has a long history as a traditional settlement for the ethnic Chinese community, with the local economy being predominantly medium to low, engaged in trading, river transport services, and household industries. Additionally, there is a diverse range of community groups with high levels of social interaction. The physical settlement aspect of the research area is predominantly residential, following a linear pattern along the Musi River and roads, with moderate to high population density. The majority of buildings are raised platform houses, and infrastructure and facilities still need further development to meet the needs of the local community.